2011
DOI: 10.1037/a0025082
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between implicit and explicit believability of exercise-related messages and intentions.

Abstract: The results indicate that exercise-related health promotion messages are believable and that the initial reaction to them coincides with reflective attitudes. However, if appearance messages are believed (even if not explicitly), the effects may be detrimental. It is important to include implicit measures in messaging research as they allow for a more complete understanding of how health messages may influence related cognitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 22 publications
1
18
1
Order By: Relevance
“…Additional research has shown that both implicit and explicit motivation are relevant to exercise: implicit measures predict the preferred properties of exercise and intention to engage in physical activity, and explicit measures predict the likelihood that these intentions will result in a change in actual exercise behaviour and in the initiation of exercise (Hagger, 2012). Researchers in this area have called for greater attention to implicit measures while pointing out that we do not yet know much about how procedures based on these measures might have their effects (Berry, Jones, McLeod, & Spence, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Additional research has shown that both implicit and explicit motivation are relevant to exercise: implicit measures predict the preferred properties of exercise and intention to engage in physical activity, and explicit measures predict the likelihood that these intentions will result in a change in actual exercise behaviour and in the initiation of exercise (Hagger, 2012). Researchers in this area have called for greater attention to implicit measures while pointing out that we do not yet know much about how procedures based on these measures might have their effects (Berry, Jones, McLeod, & Spence, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…This sample size is similar to related research [15][16]. Further, according to guidelines provided by Cohen [26], a minimum of 97 participants are needed for a regression with six predictor variables with alpha set to.05 and power = .80 and a medium effect size.…”
Section: Methodsmentioning
confidence: 95%
“…These authors contend that the type of advertising seen in popular fitness magazines such as Shape can influence body image, but there is limited research examining this issue. There is also evidence some people implicitly believe that exercise will improve one’s appearance, even if they do not explicitly report such beliefs [16]. Although media representations of beauty can result in poor body image, Thompson and colleagues also point out that acceptance of these ideals is not universal and it is possible to reject them.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations